Root cause analysis tidak tercapainya target penjualan asuransi PT. Panin Dai-Ichi Life Surabaya - Pratama, Oktaviano Ferdian; Hartini, Sri (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The Covid 19 pandemic which began to enter Indonesia in March 2020 had a profound impact on human health. This not only causes life risks, but also financial risks. That's why it is necessary to have protection that can guarantee our lives in the event of a disaster. One of them is with insurance. Various challenges in insurance marketing, of course, require that every insurance company has the right and measurable business strategy, including the Panin Dai-Ichi Life Area Surabaya Cendana insurance (hereinafter referred to as PDL). Citing sales data from 2017 to 2021, PDL obtained fluctuating policy sales. The sale also never reached the target value of rupiah sales of the policy set by the company. This research will focus on finding the root of the problem of not achieving sales targets at insurance PT. Panin Dai-ichi Life Area Surabaya Sandalwood. This type of research is a type of field research, using a qualitative approach. The subjects used were 10 Bancassurance Officers and 5 Panin Bank customers. The results obtained are on the marketing mix variable, the greatest frequency of problems is the people variable or human resources. The people variable is then processed using a fishbone diagram to find the root of the problem and 9 main problems can be found which are also formulated for strategic analysis for future improvement and development.